Self-reported nonrestorative sleep in fibromyalgia – relationship to impairments of body functions, personal function factors, and quality of life - Liedberg, Gunilla M (J Pain Res, 2015)
PURPOSE: The purpose of this study was: 1) to determine variables that might characterize good or bad sleep; and 2) to describe the relationship between sleep, impairment of body functions, personal function factors, and quality of life based on quality of sleep in women with fibromyalgia (FM). METHODS: This cross-sectional descriptive study included 224 consecutive patients diagnosed at a specialist center. These patients were mailed a questionnaire concerning sleep, body functions, personal factors, and health-related quality of life. In total, 145 completed questionnaires were collected. RESULTS: Using sleep variables (sleep quality, waking up unrefreshed, and tiredness when getting up), we identified two subgroups – the good sleep subgroup and the bad sleep subgroup – of women with FM. These subgroups exhibited significantly different characteristics concerning pain intensity, psychological variables (depressed mood, anxiety, catastrophizing, and self-efficacy), impairments of body functions, and generic and health-related quality of life. The good sleep subgroup reported a significantly better situation, including higher employment/study rate. The bad sleep subgroup reported a greater use of sleep medication. Five variables determined inclusion into either a good sleep or a bad sleep subgroup: pain in the evening, self-efficacy, anxiety, and according to the Short Form health survey role emotional and physical functioning. CONCLUSION: This study found that it was possible to identify two subgroups of women with FM based on quality of sleep variables. The two subgroups differed significantly with respect to pain, psychological factors, impairments of body functions, and perceived quality of life, where the subgroup with bad sleep had a worse situation.